FORMULATION DEVELOPMENT AND EVALUATION OF SUSTAINED RELEASE MATRIX TABLET OF ECONAZOLE (CAHIERS MAGELLANES-NS, 2024)
Abstract: - Granules made with the wet granulation process were compressible formed into sustained-release tablets for the efficient formulation of econazole. Together with excipients including talc, magnesium stearate, microcrystalline cellulose, PVP K30, guar gum, and pectin were used as binding agents. Econazole's solubility profile revealed that it was limitedly soluble in water, moderately soluble in chloroform, and highly soluble in benzene, methanol, and acetone. A range of in vitro assessments were performed on the produced tablets, including hardness, friability, weight variation, disintegration time, drug content, and dissolving behaviour tests. The release kinetics were first-order, with an R2 value of 0.983 and an equation of y = -0.077x + 2.182. Every formulation showed acceptable drug release and dissolution patterns in vitro. This study indicates that the addition of guar gum effectively adjusted the release rate, suggesting that it is a feasible technique for the creation of sustained-release matrix tablets, even if a hydrophilic matrix alone was not adequate to control the release of econazole over 24 hours.